Yahoo Web Search

  1. Sort by

  1. ... tan⁡ s/(1+cos ⁡s )+ sin⁡ s/(1-cos ⁡s )=cot⁡ s+(sec⁡ s x csc ⁡s) LHS = tan ⁡s/(1+cos⁡ s )+ sin⁡ s/(1-cos ⁡s ) (tan⁡ s(1-cos⁡ s)+sin⁡ s(1+cos...

    1 Answers · Science & Mathematics · 17/01/2012

  2. ... acting) Stand pipe is up to datum [A] in LHS figure? Then the head will be 15 m at A [ If it is...

    1 Answers · Science & Mathematics · 27/09/2011

  3. ... the above equation, ifc-ipf=(-ipc) Taking i and f common from LHS of above equation, i*f*(c-p) = i*(-pc) Eliminating i on both sides...

    1 Answers · Science & Mathematics · 07/11/2012

  4. It can't be done. It can be shown that the LHS and the RHS are not equal to each other.

    1 Answers · Science & Mathematics · 15/09/2011

  5. ...2 X^2 = C where C is an arbitrary constant The LHS is the sum of two squares so C > 0. It's...

    2 Answers · Science & Mathematics · 27/12/2009

  6. .../2t)^2) < 5000 expanding and collecting the LHS => 0.433 P D / t < 5000 Filling in the...

    7 Answers · Science & Mathematics · 10/12/2006

  7. ...5x/4 -1 = 3x - 4x/6 +9 then shifting -1 to RHS and 3x - 4x/6 to LHS, we get 2x - 5x/4 - 3x + 4x/6 = 9+1 Multiply both side by 12 24x - 15x...

    3 Answers · Science & Mathematics · 21/10/2010

  8. ...^-1 x X Since A^-1 A = E (unit matrix) LHS = E X = X RHS = x A^-1 X Or...

    2 Answers · Science & Mathematics · 07/04/2009

  9. ...u+1)/u u du/(u+1) = dx Now it's separated; to integrate the LHS, let v=u+1, so (1 - 1/v) dv = dx v - ln|v| = x + C1 u - ln|u+1| = x + ...

    2 Answers · Science & Mathematics · 02/10/2013

  10. ...all n from 1 to ∞ (note zero is not a positive integer) 2. For n=1, LHS = (a+b) and RHS = a+b so the formula holds and P(n=0) ...

    1 Answers · Science & Mathematics · 27/03/2011

  1. Ad
    related to LHS
  1. Try asking your question on Yahoo Answers